The verification of subsoil parameters based on back analysis of a bridge - Nepelski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the analysis of foundation of the road bridge. The numerical calculation of the bridge abutment was made in FEM Software with subsoil modelled as solid defined by Cam Clay model. Number of calculations was made by using variable parameters of soil. Results were compared with geodetic measurements. Soil properties designated by lab test and geological boreholes, were verified with computer back analysis results.